Consumer-provider relationships in a care coordination model of service: consumer perspectives. (2nd January 2018) - Schweizer, Richard; Honey, Anne; Hancock, Nicola; Berry, Bridget; Waks, Shifra; Scanlan, Justin Newton
ABSTRACT: Objective: The aim of this study was to identify aspects of the consumer-provider relationship that consumers saw as important in a care coordination service model. Method: Semi-structured interviews were conducted, between October 2015 and March 2016, with 20 people living with severe and persistent mental illness who used a care coordination service in Sydney, Australia. Data were analysed using constant comparative analysis. Results: Participants described five specific aspects of the consumer-provider relationship that they deemed important within their care coordination service experience: rapport and listening; an individualised approach; collaboration and partnership; reliability; and genuine care and respect. These were not independent, but rather, interdependent elements that collectively described a 'good' consumer-provider relationship. Discussion: While previous literature has examined the consumer-provider relationship in high-intensity and therapeutic models of service, this study confirms that similar relationship features are important in low-intensity or brokerage type models. Aspects such as the provider being easy to talk to and reliable appear to be of additional importance in this particular model. Findings suggest that the ability to develop trusting and collaborative relationships within a short timeframe is a critical consideration for recruitment and training of service providers working within care coordination models of service.